Marine tourism for sustainable development in Cox's Bazar, Bangladesh - Md. Anowar Hossain Bhuiyan; Abud Darda; Md. Wahidul Habib; Md. Belal Hossain (Asian Development Bank Institute (ADBI), 2020)
Marine tourism can ensure social, environmental, and economic benefits through sustainable use of marine resources. The main challenges for marine tourism are preservation of the sea and marine resources through conserving the marine ecosystems and reducing marine pollution. This tourism segment has great potential in Bangladesh with the existence of the Bay of Bengal in the southern territory of the country. The present study identifies stakeholders' perception of the development of sustainable marine tourism in the Cox's Bazar district of Bangladesh. The study is based on a questionnaire survey using a nonprobability convenience sampling design. A total of 300 respondents were purposively selected from various groups of stakeholders to give their opinions on various aspects of social, economic, and environment dimensions of marine tourism development. Results reveal that marine tourism development can ensure various elements of social well-being, such as improving quality of life, infrastructure development, and enhancing public facilities. It also has some negative impacts, such as increasing the cost of living and intense illegal activities in the study area. The stakeholders' view is that developing marine tourism brings economic benefits, such as providing employment opportunities, developing livelihoods, facilitating fishing activities, and enhancing economic well-being. However, marine tourism activities cause several environmental problems, including overcrowdedness, degradation, waste generation, imposing pressure on natural resources, and negative impacts on marine resources. Several measures, such as an environmental management plan, integrated management decisions for the local ecosystem and culture, the promotion of local goods, WTP mechanism implementation, infrastructure development, and enhanced facilities, can ensure sustainable marine tourism development in the study area.
Keywords: L83; Z31; Z32; C38; 330; Bangladesh; Cox's Bazar; marine tourism; sustainable development